Enhancement in structural and optical properties of copper tin sulphide (CTS) thin films via sulphurization process. (1st June 2022) - Hossain, E.S.; Chelvanathan, P.; Bais, B.; Azmi, N.; Shahahmadi, S.A.; Yussof, Y.; Sopian, K.; Amin, N.
Abstract: In this letter, the effects of sulphurization time on the material properties of CTS thin film and concomitant device performance were investigated. A specified range of sulphurization time from 1 to 3 hours were carried out. Structural analyses confirmed that polycrystalline CTS were apparent in all samples prepared, with an intermediate secondary phase of Cu4 Sn7 S16 which then decomposes to Cu2 SnS3 and Sn2 S3 as the sulphurization duration reached 3 h. The relative intensity of pure phase CTS was also higher in samples subjected to 3 h sulphurization duration. The FWHM was found to decrease from about 0.15 to 0.11 as the sulphurization time was extended from 1 h to 3 h. Both structural and vibrational analysis confirms that monoclinic phase CTS with a preferential orientation in (−131) direction at the diffraction angle of 28.3° was evident in all samples produced. Furthermore, sulphurization time of 3 h resulted in CTS films with the desired direct optical bandgap of 0.9 eV and largest grains. However, the presence of considerable surface voids and substantial amount of Sn2 S3 secondary phase were also detected in the sample. Nonetheless, CTS photovoltaic device fabricated using 3 h sulphurization duration recorded the highest efficiency of 0.96% with Voc = 147 mV, Jsc = 19.08 mA/cm 2, and FF = 34.27%.